Fishermen Empowerment Strategy as a Solution in the Security Management Crisis in the North Natuna Sea - Merisa Dwi Juanita; Masaji Faiz Dani Agus Setiani (Diponegoro University, 2022)
Indonesia faces tremendous pressure in dealing with the crisis in the North Natuna Sea with China, which often violates Indonesia's EEZ in the North Natuna Sea. The frequency of crises in the North Natuna Sea is increasingly frequent. It requires an effective strategy without damaging diplomatic relations, and local Natuna fishers immediately feel the benefits. Diplomatic efforts carried out since 1994 and military policies have no significant effect in preventing China's aggressiveness. Up until now, Chinese fishing vessels and the Chinese Coast Guard are still carrying out provocative actions by violating Indonesia's IUU Fishing and EEZ by adhering to the Nine-Dash Line principle, which has disrupted maritime security and has harmed Indonesia for not respecting the 1982 UNCLOS. Moreover, Jakarta's response to that event sent fishing boats from Pantura Java to take fish in the Natuna area, making it worse for local Natuna fishers. Thus act sparked a conflict, which meant Natuna fishers faced two threats from foreign parties and conflicts with Pantura Java fishers. The researcher aims to analyze the strategies that the Government of Indonesia has carried out in dealing with the crisis in the North Natuna Sea with China by using qualitative methods and triangulation analysis techniques with the concept of national interest. The researcher analyzed how the strategy used by the Indonesian Government did not have a significant impact on reducing China's aggressiveness and conflicts with Pantura Java fishers. The study results indicate that additional strategies are needed to encourage the effectiveness of the expected results by prioritizing local Natuna fishermen as part of the solution, with maximum coordination between the Indonesian Navy, BAKAMLA (Badan Keamanan Laut/ Indonesian Maritime Security Agency), and the Natuna Fisherman Community. Researchers suggest that the central Government coordinates with stakeholders to form a “Sovereignty Patrol Fisherman Team” accompanied by Bakamla as a concrete action to safeguard the sovereignty and sovereign rights of professional fishers to facilitate up-to-date and surviving fishing vessels in the North Natuna Sea as a form of state defence and empowerment of local Natuna fishers.